Thermodynamic analysis and optimization of organic Rankine cycles using 1-butylpyridinium tetrafluoroborate as a geothermal fluid / Shabnam Kazemi - Shabnam, Kazemi (2020)
Organic Rankine cycle (ORC) is a promising technology for electricity generation by utilizing heat sources at low to moderate temperature that ranges between 80-350° C. In the present work, an ionic liquid (1-butylpyridinium tetrafluoroborate, C9H14NBF4), a known green chemical and non-volatile compound with good thermal and chemical stability, significant heat capacity, low vapor pressure and a wide liquid temperature range (25 to 459 °C), is utilized as a geothermal fluid. Simulation and optimization were conducted for a basic organic Rankine cycle (basic ORC), a regenerative organic Rankine cycle (RORC) and a two-stage evaporative organic Rankine cycle (TSORC) by maximizing exergy efficiency and minimizing specific investment cost. The operating parameters considered in the optimization exercise were evaporative and regenerative temperatures, pinch point temperature difference of evaporators and the degree of superheat. Peng Robinson equation of state was used, and isobutane (R-600a) and butane (R-600) were selected as working fluids. Comparisons were made between the performance of ORCs when C9H14NBF4 and water were individually used as a geothermal fluid. Utilization of an ionic liquid improved the performance of the three ORC configurations with the best performance generated from a basic ORC with exergy efficiency of 82.35% (R-600) and 87.70 %(R-600a). From an economic viewpoint, the amount of specific investment cost (SIC) is comparatively lower when ionic liquid is used as a geothermal fluid.